První česká antropologická monografie: Josef Voráček: Počátky vlastnictví a práva ve světle etnologie a sociologie (1936) - Voráček, Josef (Lidé města, 2018)
The first – unsuccessful – attempt at establishing social or even general anthropology in the Czech environment was the work of Josef Voráček, dating to the interwar period. As yet, the works of Voráček have not been the focus of the analysis they deserve; however, they are easily available – with one exception, i.e. the brochure introducing the first Czech anthropological monograph entitled The Beginnings of Ownership and Law from the Perspective of Ethnology and Sociology from 1936. This work, obviously stemming from the analytical and interpretative tradition of the “ethnology” of Mauss, primarily uses the methodology used in philosophical anthropology. We are therefore introducing it to the readers. The author attempts to construe the primordial relation between property rights and magic, and it assumes that the first property of man was their body and their personal effects, from which he derives consequences for property-law and social relations in pre-logical societies, as well as what remained of them in later periods of cultural development.